Relasi Gender dalam Hubungan Pacaran - Aldies Nur Fadilah; Netty Dyah Kuniasari Kuniasari; Dewi Quraisyin Dewi Quraisyin (Jurnal Komunikasi, 2011)
This study aims to determine the gender relations in the communication process that occurs in adolescents who are dating and to find other forms of verbal and non verbal violence in adolescent dating couples are. The method used is a qualitative method with case study approach. Techniques of data collection in this study using primary data that is interview and observation data as well as secondary data from books and media. Subjects in this study is that dating adolescents residing in Bangkalan. In this study there were five informants dating couples. The results of this study is the existence of gender differences in expressing feelings in which men are more dominant in expressing feelings than women, then men prefer women prefer to touch and be touched, the difference in resolving conflicts in which men more than to start a conversation apologizing women, in addition there are also verbal abuse in the form of calls that are not worthy of love and affection the call changes in the text. Non verbal violence is the presence of physical violence in the form of beatings and psychological violence in the form of restraint, hurt, cheating and lied to. Violence a man is to be hurt from the women, psychological violence.Key words: Communication interpersonal-psychoanalytic feminism-dating-inrelationship